High performance III-V photoelectrodes for solar water splitting via synergistically tailored structure and stoichiometry - Haneol Lim (Nature Portfolio, 2019)
Photoelectrochemical water splitting presents an integrated means storing sunlight into fuels, yet high optical losses and corrosion limit device performance. Here, authors boost absorption and durability in gallium-indium phosphide photocathodes via a sulfurized and nanostructured protection layer.